ANALISIS KELAYAKAN PENGEMBANGAN EKOWISATA DI KAWASAN MANGROVE LEARNING CENTRE (MLC) BALUNO, SULAWESI BARAT: Feasibility Analysis of Ecotourism Development on The Baluno Mangrove Learning Centre (MLC) Area in West Sulawesi - Rita Bulan; Uswatun Khasanah; Pipin Noviati Sadikin (Bogor Hospitality Journal, 2024)
Mangrove Learning Center (MLC) Baluno is one of the tourist destinations in the mangrove area that can be developed with the ecotourism concept. This study aims to calculate the potential value of the supply and the feasibility index of mangrove ecotourism development in the MLC Baluno area. The method was qualitative research. Data collection was carried out through observation, interviews, documentation studies and literature reviews. Data analysis used a modification of the Operational Area Analysis Development Criteria approach - Natural Tourism Attraction Objects (ADO-ODTWA) of PHKA (Forest Protection and Nature Conservation); and Ecotourism Development Criteria of Damanik and Weber’s method. The results of the study showed that the MLC Baluno area has a potential supply value of 2,590 (moderate classification) and is included in the category of being feasible to be developed as an ecotourism area based on the identified feasibility index of 73.89%.